Scalable exfoliation and friction performance of few-layered WS2 nanosheets by microwave-assisted liquid-phase sonication. Issue 3 (15th February 2020) - Ma, Lu; Liu, Zan; Cheng, Zhi-Lin
Abstract: The convenient and high efficient exfoliation for few-layer nanosheets was indispensable for their potential applications. In fact, many reported approaches have been used to successfully exfoliate bulk layered materials into few layers, which fundamentally confronted a few challenges in practice, such as high cost, complicate process, low efficiency and environmental problem. Hence, developing the novel exfoliation process without the above issues was imperative to the prospective application of nanosheets. In this work, we presented a facile and high-quality exfoliation process for few-layer WS2 nanosheets via microwave-assisted sonication method. Detailedly, the crucial highlight in this process was employed the microwave heating expansion via the decomposition of ammonium carbonate pre-impregnated in the interlayers of bulk layered WS2, which was conductive to the second-step liquid phase sonication. The structure characterizations of the as-exfoliated WS2 nanosheets revealed that the high-quality nanosheets had the average lateral size of ca.400 nm and thickness of ca.2.33 nm. Additionally, the tribological performance of the as-exfoliated WS2 nanosheets in oil was investigated, showing that the average friction coefficient of the WS2 -based oil was reduced by 28.47% and the wear scar diameter was decreased by 51.67% compared to pristine oil.